Highly Conductive Cellulose Network/Polyaniline Composites Prepared by Wood Fractionation and In Situ Polymerization of Aniline. Issue 7 (16th April 2019) - Ke, Shaoqiu; Ouyang, Tulong; Zhang, Kai; Nong, Yuhong; Mo, Ying; Mo, Qiufeng; Wei, Yongxuan; Cheng, Fangchao
Abstract: Highly conductive cellulose network/polyaniline (PANI) composites are successfully formed using chemical fractionation of solid wood followed by in situ polymerization of aniline monomers in the purified wood. The increased porosity of the wood caused by the fractionation process enables the uniform deposition of PANI particles in the microstructure of the material, resulting in a high electrical conductivity of up to 36.79 S cm −1, and a high weight gain rate of up to 143%. The interaction between PANI and the cellulose microfibril network leads to a decreased crystallinity of the composites. The electrode prepared from the cellulose network/PANI composites exhibits promising gravimetric specific capacitances of up to 218.75 F g −1 and areal specific capacitances of up to 0.41 F cm −2, and it can be assembled into all‐solid‐state supercapacitors with favorable energy storage performance, which may be attributed to the larger surface area, higher PANI content of the electrode, and the positive effect of the cellular structure of the cellulose network on electron transport. The present process can preserve the naturally hierarchical structure of wood and impart a promising conductivity to the composites, and it provides a promising way to produce hierarchical biomass‐based electronic materials for high‐performance storage field. Abstract : Cellulose network/polyaniline composites possessing hierarchical porous nanostructure of wood exhibits high conductivity and promising specific capacitance when used as electrode materials. The natural structure of the cellulose network provides an extremely wide space for its performance improvement, and it can be used as a platform for the development of sustainable high‐performance electrode materials.